Özel Eğitim Kurumlarının Fiziksel Koşullarının Evrensel Tasarım İlkeleri Doğrultusunda İncelenmesi: Eskişehir Örneği - Kaplan, Gamze; Aksoy, Veysel (İstanbul Kültür Üniversitesi / Eğitim Fakültesi, 2019)
Universal design is the design of products, services and environments so that they can be accessed and used to the greatest extent possible by all people, without the need for adaptation and specialized design. This study aims to examine the physical conditions at special education and rehabilitation centres in Eskişehir based on the principles of universal design. The participants for this study were selected from 13 centres in the province of Eskişehir. Descriptive survey model was used for this examination. The data collected with “Universal Design Checklist” were obtained through direct observation, and analysed using frequency (f) and percentage (%). The findings of the analysis were approached from two perspectives: the number of the centres, and the scores they got from the checklist. The examination of the findings shows that the sections with the highest average are the “features related to classrooms” and “emergency exits and emergency situations”, with the lowest average being the “features of physical accessibility” and “toilets”. The findings were discussed based on the related literature.

Evrensel tasarım, uyarlama ve kişiye özel tasarım ihtiyacı olmaksızın tüm insanlar tarafından mümkün olan en geniş ölçüde kullanılabilen ürün, hizmet ve ortamların tasarımı olarak tanımlanmaktadır. Bu araştırmada Eskişehir ilinde yer alan özel özel eğitim ve rehabilitasyon merkezlerinin fiziksel koşullarının evrensel tasarım ilkeleri doğrultusunda incelenmesi amaçlanmaktadır. Araştırmada nicel araştırma yöntemlerinden betimsel tarama modeli kullanılmıştır. Katılımcı grubu olarak Eskişehir ilinde yer alan on üç kurum belirlenmiştir. Araştırmacılar tarafından geliştirilen "Evrensel Tasarım Kontrol Listesi" ile toplanan veriler doğrudan gözlem yoluyla elde edilmiştir. Elde edilen veriler frekans (f) ve yüzde (%) olarak analiz edilmiştir. Yapılan analiz doğrultusunda bulgular, maddeleri karşılayan kurum sayısı ve kurumların kontrol listesinden aldıkları puanlara göre iki açıdan ele alınmıştır. Elde edilen bulgular incelendiğinde en yüksek ortalamaya sahip bölümlerin dersliklerle ilişkili özellikler ve acil çıkış ve acil durumlar olduğu görülmektedir. En düşük ortalamaya sahip olan özelliklerin ise fiziksel erişilebilirlik unsurları ve tuvaletler olduğu görülmektedir. Bulgular ilgili alanyazın doğrultusunda tartışılmıştır.
An Examination of the Physical Environment at Special Education Centres in Eskişehir Based on Universal Design Principles
Keywords: Evrensel Tasarım; Erişilebilirlik; Ulaşılabilirlik; Sosyal Model; Universal Design; Accessibility; Availability; Social Model